The landscape of public service innovation in Indonesia: A comprehensive analysis of its characteristic and trend - Arif Budy Pratama (Innovation & Management Review, 2020)
Purpose - The purpose of this paper is to provide a comprehensive analysis of Indonesia's public service innovation drawn from the top 99 nominees of the national competition for public service innovation from 2014 to 2016. Design/methodology/approach To answer the research question, this study applied archival research as a research strategy. A documentation method was conducted to collect the data. Using content analysis aided by NVivo 11 this study analyzes the following themes: implementing agencies, innovation types, innovation goals, innovation outcomes, policy sector in which innovation implemented and geographical perspective. Findings The public service innovation in Indonesia from 2014 to 2016 were dominated by local government and process innovation in which designates to the amalgamation of technological and administrative dimensions of innovation. The most occurrence outcomes were aimed to tackling societal problems in the health and education sector. Whilst in the geographical perspective, big portion of innovation were taking place in Java Island. Research limitations/implications The result of this study is mainly based on secondary data drawing from public service innovation competition held by the Indonesian Ministry of Administrative Reform. Consequently, the result is limited to provide a mapping feature and trends of innovation. Future research may use more extensive samples (not only sourced from the nominees but also all submitted initiatives) to obtain more representation of public service innovation in Indonesia. Practical implications Given the fact that lack of collaboration between public and private actors, the government needs to consider on designing strategies and policy direction to foster collaboration in public service innovation. Originality/value This research offers a comprehensive analysis on Indonesian public service innovation. Methodologically, the research introduces archival research as one of the alternative research strategies on public sector innovation scholarships.
Keywords: 650; Content analysis; Archival research; Innovation types; Innovator; Public service innovation